Fingerprint Gender Classification Using Univariate Decision Tree (J48) - Abdullah, S.F; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida; Mohd Saad, Wira Hidayat (The Science and Information (SAI) Organization Limited, 2016)
-